Temperature variation effect on crack growth in orthotropic medium: Finite element formulation for the viscoelastic behavior in thermal cracked wood-based materials. (1st June 2017) - Hamdi, Seif Eddine; Pitti, Rostand Moutou; Dubois, Frédéric
Abstract: The occurrence of cracks and loss of mechanical properties are major problems in wood-based structures. A proper understanding of the mechanism of thermal contraction cracking often results in the formation of such cracks being incorrectly attributed to other causes such as plastic or drying shrinkage, is necessary in order to avoid this form of defects. The presented work tries to investigate the influence of temperature expansion on crack driving forces through an incremental finite element based approach. Mixed-mode crack growth analysis coupling mechanical and thermal loads in orthotropic wood-based materials is conducted. The viscoelastic analytical formulation of creep crack growth process under thermal loading is introduced by A-integral, based on an energetic approach using conservative laws. A numerical validation in terms of local fracture characteristics, is carried out on a Mixed Mode Crack Growth (MMCG) specimen under mixed mode configurations for different crack growth configuration. The effect of thermal loading coupling with viscoelastic effect is shown in wood material for all mixed mode configurations.